Attempt to Train Computational Thinking Skills Among Students of SMP Negeri 5 Indralaya Utara, Tanjung Baru Village: Introduction and Training on the Using of Basic Coding Through the Pictoblox 4.0 Application - Evelina Astra Patriot; Hamdi Akhsan; Ketang Wiyono; Saparini; Maghfira Aulia; Nor Farahwahidah Abdul Rahman; Noor Dayana Abd Halim; Nia Three Manurung; Isma Sari; Putri Wijayanti; Dendi Juliansyah; Tina Oktasari (Pascasarjana Universitas Mataram, 2025)
Current technological developments require the education sector to engage in continuous innovation to advance the quality of future generations. Coding and artificial intelligence are forms of innovation that can be integrated into learning activities. To equip students with these skills, this community service program aims to introduce and train students in the use of simple block coding through the use of 4.0 applications. The training and community service activities were carried out over a period of 3 months with a target of 25 junior high school students in Tanjung Baru Village. The training was carried out through a series of activities, namely (a) conducting a preliminary test; (2) delivering material on the use of block coding for learning, the use of the Pictoblox 4.0 application, and the creation of simple games and chatbots; and (3) conducting a final test. The N-gain percentage result was 89.5%. This percentage is high, indicating that there is a significant effect on improving students' computational thinking skills. The implementation of this activity had a positive impact on the training participants. This is demonstrated by the evaluation results, which indicate that this community service activity will continue with other innovative activities. The implication of this community service activity is to provide innovative coding and artificial intelligence learning activities that are integrated into the curriculum.